Kick some glass : 10 ways women succeed at work on their own terms - Martineau, Jennifer; Mount, Portia (McGraw Hill-Ascent Audio, 2018)
The rule-smashing guide for motivated working women who want to stop following someone else's rules and take charge of their own success. You leaned in like a palm tree in a hurricane. You cracked the confidence code. You're determined not to be a nice girl, but a #GirlBoss. You've learned you can't have it all, but you still try anyway. You know all of this. You've read the books, downloaded the apps, vision boarded and journaled your way to oblivion and back, to no avail. Whether you're stuck in middle management, stalled in mid-career, or mulling over a major career change, sometimes the proverbial glass ceiling feels very real indeed-a barrier keeping you from fulfilling your potential. Unlike other books, which focus on fixing you, Kick Some Glass empowers you to break through your glass ceiling and guides you toward understanding your context and uncovering what you really want, what your definition of success is, what your values are, and how to set the goals to reach your potential. This is no one-size-fits-all career guide. It's a top-to-bottom, inside-out, do-it-yourself makeover with the focus completely on you. In each chapter, you'll be asked to evaluate specific parts of your work life, home life, personal strengths and weaknesses, past history and present obstacles, both internal and external, so you can: * Live your intention and design a meaningful life at any stage * Identify the underlying values that are the core of your being * Get comfortable with your personal power and understand what it means * Uncover the conscious and subconscious mental models that are holding you back * Take calculated risks through planful action with a clear direction * Let go of things you cannot control or change * Become more resilient, adaptable, and self-aware * Make the choices and tradeoffs necessary to fulfill your goals * Decide if it's time to reinvent your career-and prepare for your next move * Find that elusive work-life balance that's right for you * Create your own definition of success-and make it happen for you Best of all, you'll be able to map out a career course for yourself that is based on your own definition of success, play and win by your own rules, and pay it forward by busting down doors for the next generation of women. In the end, this book will help you uncover who you truly are and approach your professional life in ways that are authentic and most meaningful to you-and no one else. After all, only you hold the answers. It's time to Kick Some Glass.